Performance Enhancement of İnverted Type Organic Solar Cells By Using Eu Doped TiO2 Thin Film - Örnek O.; Kösemen Z.A.; Öztürk S.; Canımkubey B.; Fındık Ş.; Erkovan M.; Kösemen A. (Elsevier B.V., 2017)
In the present work, europium (Eu) has been used as a dopant element in titanium dioxide (TiO2) crystal structure to enhance the photovoltaic performance of the inverted type organic solar cells fabricated with TiO2 thin film as an electron transport layer. Poly(3-hexylthiophene):phenylC61-butyric acid methyl ester (P3HT: PCBM) blend has been used as an active layer and Eu:TiO2 thin films have been fabricated with different Eu concentrations as 0, 1, 5, 7 and 10% (w/w) by sol-gel method. Effect of Eu doping concentration on the photovoltaic performance of the inverted type solar cells has been investigated. Inverted type organic solar cells using Eu doped TiO2 thin films as electron transport layer has been fabricated as a structure of ITO/Eu:TiO2/P3HT:PCBM/Ag. Power conversion efficiency of the fabricated solar cells increased from 1.16% to 2.47% at 5% Eu doping concentration. Electron transport and hole blocking properties of the TiO2 inter layer has been improved by Eu doping. © 2017 Elsevier B.V.
Keywords: Doping of metal oxides; Impurities in semiconductors; Oxide materials; Photoconductivity and photovoltaic; Sol-gel processes